Peran Podcast dalam Penginjilan Digital, Upaya Gereja terhadap Misi dan Pembentukan Etis Teologis Jemaat di Era disrupsi - Suseno, Aji; Arifianto, Yonatan Alex; Rahayu, Yohana Fajar (Ritornera - Jurnal Teologi Pentakosta Indonesia, 2025)
The development of internet of thoughts technology, in an era of increasingly massive digital disruption, the church faces new problems in delivering the message of the Great Commission. Where busyness and the internet that changes the culture of communication becomes a new opportunity in digital mission. One of the tools that is now increasingly popular is podcasts, a medium that allows evangelism to be carried out more flexibly and accessibly. The role of podcasts in digital evangelism is becoming increasingly relevant given the high internet penetration and people's preference for audio content consumption. This study aims to examine how churches utilise podcasts as a tool to support evangelistic missions and theological ethical formation of congregations in the midst of changing times. Using a descriptive qualitative method with a literature study approach and content analysis of podcasts uploaded on digital platforms.  The conclusions of the findings of this study indicate that digital mission is actually in the order of the Great Commission. and the role of podcasts in digital evangelism provides new opportunities for wider and deeper evangelism, expanding the reach of the gospel message among all audiences. This is what educates the church in building a culture of mission and forming digital ethics. although there is an influence of digital evangelism on the mission of the church, the formation of digital ethics in evangelism. this is an opportunity and challenge in digital evangelism through podcasts. In addition, podcasts are also an important tool in shaping theological understanding and church ethics that are more relevant in this era of disruption.  Therefore, the church can utilise podcasts as a medium that is adaptive to cultural and technological changes, strengthening the relevance of evangelistic mission in a changing world.AbstrakPerkembangan teknologi internet of Thinks, di era disrupsi digital yang semakin massif, gereja menghadapi persoalan baru dalam menyampaikan pesan  Amanat Agung. Di mana kesibukan dan internet yang merubah budaya komunikasi menjadi peluang baru di misis digital. Salah satu sarana yang kini semakin populer adalah podcast, sebuah media yang memungkinkan penginjilan dilakukan secara lebih fleksibel dan aksesibel. Peran podcast dalam penginjilan digital menjadi semakin relevan mengingat penetrasi internet yang tinggi dan preferensi masyarakat terhadap konsumsi konten audio. Penelitian ini bertujuan untuk mengkaji bagaimana gereja memanfaatkan podcast sebagai alat untuk mendukung misi penginjilan dan pembentukan etis teologis jemaat di tengah perubahan zaman. Menggunakan metode kualitatif deskritif dengan pendekatan studi pustaka dan analisis konten podcast yang diupload di platform digital.  Adapaun kesimpulan dari temuan  penelitian ini menunjukkan bahwa sejatinya digital misi dalam perintah Amanat Agung. dan peran podcast dalam penginjilan digital memberikan peluang baru untuk penginjilan yang lebih luas dan mendalam, memperluas jangkauan pesan Injil di kalangan semua audiens. Hal inilah yang menjadi edukasi jemaat dalam membangun budaya misi dan membentuk etika digital. walaupun adanya pengaruh penginjilan digital terhadap misi gereja pembentukan etika digital dalam penginjilan. ini menjadi kesempatan dan tantangan dalam penginjilan digital melalui podcast. Selain itu, podcast juga menjadi sarana penting dalam membentuk pemahaman teologis dan etika gereja yang lebih relevan di era disrupsi ini.  Maka itu gereja dapat memanfaatkan podcast sebagai media yang adaptif terhadap perubahan budaya dan teknologi, memperkuat relevansi misi penginjilan dalam dunia yang terus berubah.